Soft Computing Techniques ABC, IABC and SFL Optimization Algorithms for 15 Unit Thermal Generating Systems (International Journal of Engineering and Computer Science, 2017)
this paper presents an analysis of Economic Load Dispatch (ELD) problem using various algorithms such as ABC, IABC and SFL algorithm in order to maintain a high degree of economy and reliability of the power system. The primary objectives of this paper is to develop flexible and extensible computational framework as MATLAB environment for implementing the various algorithms such as ABC ,IABC and SFL to solve economic load dispatch problem and analysis the Performance of various optimization algorithms on the basis of  power generation(MW),computational time(sec) ,minimum generation cost(INR) and power loss(MW).